1999
DOI: 10.1001/archpsyc.56.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Methylphenidate Therapy in Children With Comorbid Attention-Deficit Hyperactivity Disorder and Chronic Multiple Tic Disorder

Abstract: Background: This study examined changes in attentiondeficit hyperactivity (ADHD) behaviors and motor and vocal tics during long-term treatment with methylphenidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
4

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(60 citation statements)
references
References 39 publications
1
55
0
4
Order By: Relevance
“…146 -148 Two naturalistic studies have examined the long-term effects of stimulants in TS. 149,150 The findings of these studies suggest that children with ADHD and tics do not invariably manifest an increase in tics upon exposure to stimulant medication, though an exacerbation in tics may occur in some cases.…”
Section: Treatment Of Adhdmentioning
confidence: 91%
“…146 -148 Two naturalistic studies have examined the long-term effects of stimulants in TS. 149,150 The findings of these studies suggest that children with ADHD and tics do not invariably manifest an increase in tics upon exposure to stimulant medication, though an exacerbation in tics may occur in some cases.…”
Section: Treatment Of Adhdmentioning
confidence: 91%
“…31,64,65 With respect to tics, it is thought that stimulant medication may precipitate their onset but does not cause them. 49 Gadow et al (1999) conducted a long-term study of children with ADHD and multiple tic disorder. 66 The children, who had multiple tic disorder prior to psychostimulant therapy, were evaluated at six-month intervals for two years.…”
Section: Adverse Reactions and Side-effects Of Stimulant Treatmentmentioning
confidence: 99%
“…49 Gadow et al (1999) conducted a long-term study of children with ADHD and multiple tic disorder. 66 The children, who had multiple tic disorder prior to psychostimulant therapy, were evaluated at six-month intervals for two years. Overall, methylphenidate did not exacerbate the children's motor or vocal tics.…”
Section: Adverse Reactions and Side-effects Of Stimulant Treatmentmentioning
confidence: 99%
“…Since then, a group of well-controlled studies has reported that MPH and d-AMP are effective, well tolerated, and safe in children with tics. 80,81 On average, tics improve rather than deteriorate when exposed to stimulant medication. 80 However, if tics occur or worsen during a trial of stimulants, an alternative stimulant or a nonstimulant such as atomoxetine should be tried.…”
Section: Medication and Ticsmentioning
confidence: 99%
“…80,81 On average, tics improve rather than deteriorate when exposed to stimulant medication. 80 However, if tics occur or worsen during a trial of stimulants, an alternative stimulant or a nonstimulant such as atomoxetine should be tried. 82 Combined therapy with an alpha-agonist or antipsychotic agent is often effective and safe in children whose ADHD symptoms respond only to a tic-inducing stimulant.…”
Section: Medication and Ticsmentioning
confidence: 99%